Features of the lean production implementation at the enterprises of ukraine’s dairy industry - Foshchii, Mariia; Krasnokutska, Natalia (Baltija Publishing, Riga, Latvia, 2021)
The purpose of the paper is to study the features of the lean production implementation in the dairy industry of Ukraine. Methodology. To achieve the purpose and solve the tasks set in the paper, a system of general and special research methods was used, namely methods of scientifi knowledge (scientifi abstraction, analysis and synthesis, deduction, generalization) to study the theoretical principles of the lean production implementation in Ukraine’s enterprises, and questionnaire to assess the lean production implementation’s effctiveness in the enterprises of Ukraine’s dairy industry. Results of the survey examine the theoretical and methodological foundations of the “lean production” concept: taking into account all the defiitions mentioned above, the following author’s defiition of lean production is put forward: lean production is a system of the enterprise, which is constantly improving, aimed at building all processes in a continuous flw of value creation by preventing and eliminating all types of losses, involving staf in teamwork based on project approaches and maintaining safe working conditions in order to create attractive value for the consumer. Methodological support for rapid assessment of the lean production implementation’s effctiveness on the basis of employee surveys has been developed and the effiency of the lean production implementation at the enterprises of Ukraine’s dairy industry has been assessed. It is concluded about the lack of effctiveness of implementing lean production at three enterprises of Ukraine’s dairy industry. This is due to the short period of the lean production implementation, as Enterprise 1 only started implementation at the end of 2020. Based on the survey and questionnaire of employees and managers of Ukraine’s dairy industry, the main stereotypes related to the implementation of lean production are identifid and refuted, and the reasons for the slow and ineffient implementation of lean production are identifid. Lean manufacturing cannot be implemented once and for all, it must be done constantly, because lean manufacturing is a tool for gaining a competitive advantage. Scientifi novelty: methodological support for rapid assessment of the lean production implementation’s effctiveness has been further developed, which, unlike others, takes into account the peculiarities of the dairy industry and allows to determine problems and prospects for enterprise development on the basis of a questionnaire. A promising direction of research is a more detailed analysis of the “lean production polygon”, which is based on the survey. A more detailed analysis of the underlying three pentagons will reveal problems in the three subsystems of lean production.
Keywords: lean production; concept; implementation of lean production; effiency assessment; problems of the lean production implementation